PERLINDUNGAN HUKUM BAGI KONSUMEN DALAM JUAL BELI SECARA ONLINE MENURUT UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Ainul Masruroh (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2019)
The purpose of this study is to explain and understand the regulation of online trading in Indonesia and to juridically analyze how legal protection for consumers in buying and selling online in accordance with Law Number 8 of 1999 concerning Consumer Protection. The method used in this thesis is a type of normative juridical research. The approach to the problem used is the legal approach (sculpture approach) and the conceptual approach (conceptual approach). This thesis uses three types of legal material sources, namely primary legal material, secondary legal material and tertiary legal material. The conclusions of this study are: that online buying and selling transactions have developed rapidly in Indonesian jurisdiction and users of these transactions are large enough to need special rules to protect transaction activities so that consumers protect themselves from all kinds of bad faith and Indonesia itself has a legal basis regarding consumer protection, including Law Number 8 of 1999 concerning Consumer Protection. Consumers who buy and sell online or E-Commerce must be given special protection that can protect business people who have bad intentions in making online buying and selling transactions.